Practical configured microtremor array measurements (MAMs) for the geological investigation of underground space - Moon, Sung-Woo; Ku, Taeseo; Palanidoss, Subramaniam; Zhang, Yunhuo; Wei, Xiao; Huang, Ean Seong; Kumarasamy, Jeyatharan; Goh, Kok Hun (Elsevier, 2020)
Underground space utilization is becoming increasingly essential for modern metropolitan cities such as Singapore. Mapping a soil/rock interface using traditional borehole investigation methods is expensive and difficult, owing to the numerous physical constraints within a built-up city. Boreholes are often far apart, resulting in many unforeseen ground conditions during subsequent excavation. Geophysical methods are sometimes employed as possible alternatives for fast, economical, and efficient bedrock surveys. The goal of this study is to investigate the practical details of applying microtremor array measurement (MAM) as a non-invasive surface wave survey for mapping soil/rock interfaces in Singapore. Critical configurations in field data acquisition are examined, and practical recommendations for array construction are provided. In addition, 30 in situ MAM tests are carried out for two major geological formations in Singapore. From the results, a standard shear wave velocity (Vs) of 500 m/s is found to be suitable for interpreting the soil/rock interface, for the Bukit Timah Granite and Jurong formations. However, the method does not predict well when soft Kallang formation deposits are present. Other limitations are also discussed in the later parts of this paper. Conclusions and practical recommendations are discussed, providing constructive guidance to the industry. The proposed Vs-based method and associated guidelines and limitations can be used to create a digital geological database and are especially useful for rock profiling in an urban environment.